History and culture of south India: discoveries in coastal Karnataka Vol I - BHAT (P Gururaja) (Udupi -, 2010)
History and Culture of South India encapsulates Dr. Bhat's effort to chronologically locate temples of coastal Karnataka, and the icons installed in them.
Keywords: South Kanara; South Canara; Temples South Kanara